Aktivitas seksual dan perilaku seks pranikah pada mahasiswa - Tholense, Natalia; Rahardjo, Wahyu (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2013)
The purpose of this study is to examine the correlation between sexual assertiveness and premarital sexual behavior in female college students. Participants of this research is 100 female college students from Gunadarma University in Jakarta. The result shows that sexual assertiveness has negative signiicant correlation to premarital sexual behavior. This inding shows that women, especially female college students has to develop sexual assertiveness in order to keep away from premarital sexual behavior.